Microfluidic generation of bacterial biohybrids for magnetic guidance and content release - OToole,N; Allen,ME; Contini,C; Elani,Y (Chemical Communications, 2025)
Bacterial biohybrids use bacterial and synthetic components for biotechnological applications. Here, we outline an adaptable and high-throughput microfluidic platform to create microscale biocontained bacterial biohybrids enclosed in a hydrogel with magnetotactic and biosensing properties. The biohybrids are capable of magnetically driven motility, biochemical sensing and controlled cargo release. This approach enables the scalable fabrication of biocontained multifunctional biohybrids for potential industrial and biomedical applications.